Integration of self-efficacy in digital-based physical training in increasing physical activity of young women - Ilham; Oktadinata, Alek; Nugraha, Ugi; Yuliawan, Ely (UIR Press, 2023)
This study aims to test the integration of self-efficacy into physical training digitally by increasing the physical activity of young women. Social Cognitive Theory (SCT), by integrating self-efficacy in training and rehabilitation programs, has been used to address health problems. With the help of social support, a person's physical activity can be predicted. This study is based on the low physical activity of young women during the COVID-19 pandemic, which can affect the quality of health and social development. This study is an experimental study using a randomized pretest-posttest control group design. The instrument used to collect the data is the International Physical Activity Questionnaire (IPAQ) for young and middle-aged adults (15–19) and then processed with independent t test analysis techniques. The results of the average scores of knowledge, attitudes, and levels of physical activity in the control group did not differ markedly before and after the intervention. Whereas in the experimental group, the difference before and after the intervention was significant (t count = 6.9159; t table 1.6848 and 2.022; t count > t table), and the average value of the aforementioned factors increased after the intervention. The results of this study revealed that the use of digital media in physical exercise with the integration of self-efficacy can increase the physical activity of young women, and digital media can be effective in improving health-based behaviors. Sociodemographic variables such as the level of motor skills appear to be significant predictors of self-efficacy for coping with sedentary behavior. Understanding self-efficacy predictors for coping with sedentary behavior can help physical education integrate the emotional dimensions of health into physical education interventions, identify groups based on level, customize messages, and prioritize resources in shaping pro-health behavior.